WateriD User Manual. - Uslu, Berk (Iwa Publishing, 2014)
Agencies are investing enormous resources into asset management programs for their water and wastewater piping systems, including comprehensive asset condition assessments and predictive maintenance programs, which lead to asset renewal prioritization and scheduling. Unfortunately, once assets are scheduled for renewal, the concepts of asset management are then largely ignored. Without a holistic approach of "cradle to grave" sustainable asset management integration and implementation, the true cost-savings of asset management cannot be achieved. Asset management principles particularly need to be applied to the actual renewal programs, but knowledge gaps in the industry are generally precluding such implementation. The Water Infrastructure Database (WATERiD) is intended to help to bridge this knowledge gap so that the true promise of asset management can be achieved. WATERiD is designed to be a knowledge base where water and wastewater utilities can upload and gather information about the asset management technology and practice experiences. Although there is some information publicly available on the website (case studies, paper reviews, technology profiles, etc.), most of the information can only be accessed by registering onto the website and logging in with a personal username and password. This manual is designed to guide users so that they can use the website efficiently and seamlessly. It contains detailed information about the website and the database structure, how to navigate the website, how to upload and gather information, and answers frequently asked questions by users. Most of the titles are directly linked to the pertinent part of the database. Therefore, users can click on these hyperlinks to access the part of the website explained in the user manual.